Answer:
infinite solution
Step-by-step explanation:
if substitute 3y+4Into 3x your equation should be 3(3y+4)-9=12 then you multiply and combine like terms then your answer should be 12=12 which is a true statement meaning it has infinite solutions
Answer:
attached below
Step-by-step explanation:
Answer:
C. Australia and Antarctica were a single landmass in the past.
Step-by-step explanation:
The most likely explanation for why the fossils of this plant are found on these two continents is that Australia and Antarctica were a single landmass in the past.
This evidence is vastly supported by the theory of plate tectonics originally, the theory of continental drift.
Plate tectonics proposes that all land masses were once joined together as a single supercontinent called Pangaea.
The region of Antartica and Australia were once joined as a single continental mass.
The plant must have developed together at that time.
When the continents moved apart, they still had the fossils.
Answer:
36=b^2 or b=the square root of 36
Step-by-step explanation:
The sides of a square are all equal in length. To find the area of a square you can multiply the two sides together. Considering that they are the same length, you can just square one of the side lengths to get your answer. To find a side length you can take the square root of the area.
Answer:
Step-by-step explanation:
b · b = 36
If Whitley park is a rectangular park with a perimeter of 70 yards. One side of Whitley park is 18 feet long then 174 yards is the area.
Area of rectangle is length times of breadth.
We know that 18 feet=6 yards.
It is given that One side of Whitley park is 18 feet long, so one side of length is 6 yards.
2(Lenght+breadth)=70
2(L+6)=70
2l+12=70
2l=70-12
2l=58
l=29 yards
Now
Area =Length×breadth
=29×6
= 174 square yards
Hence 174 square yards is the area of Whitley park.
To learn more on Area of Rectangle click:
#SPJ2
Answer:
174 yards squared
Step-by-step explanation:
Answer:
The other number is 5/9.
Step-by-step explanation:
16/3 = 48/5 * x
x = 5/9
Answer:
-q
Step-by-step explanation:
We know that we are trying to find an expression equivelant to p - q:
p - q can be p - 1q
We can then put parenthesis around -1q:
p + (-1q)
We then can simplify:
p + (-q)